Confidence as a Buffer Against Covid-19 Stigma: Enhancing Employee Engagement Among Recovered Individuals - Fatima Ashraf (National University of Modern Languages (NUML), Islamabad, 2024)
Quality of work life (QWL) is important for individual and organizational success.  Post-pandemic times have brought the challenge of declined, yet continued Covid-19 cases among the working Pakistani population. Stigma due to Covid-19 and thus deteriorated QWL in such individuals is plausible. Hence, elucidating factors that enhance the possible damaged quality of work life among Covid-19 stigmatized individuals remains an essential question for managers and practitioners. Drawing on the Social Identity theory, we hypothesize that QWL is damaged in Covid-19 recovered, stigmatized working individuals through deterioration in self-esteem as such individuals are prone to influences from the societal groups that they psychologically identify with. We also argue that self-efficacy buffers this negative effect. Albeit several researches have probed into relations of QWL with stigma-related antecedents and moderation and mediation mechanisms that underlie these effect, but this study investigates self-esteem and self-efficacy as mediator and moderator, respectively, of the Covid-19 related stigma and quality of work life relationship through the lens of the Social Identity Theory. Employing a correlational framework using purposive sampling, we obtained data from 133 working individuals who had been tested positive with Covid-19 in public and private hospitals and health centers of Pakistan during November 2022 - November 2023, had completely recovered and joined their professional lives. Results confirmed study hypotheses, suggesting that stigma related to Covid-19 damages QWL, this relationship is mediated by self-esteem, while self-efficacy buffers the relationship between Covid-19 related stigma and self-esteem. Such individuals and their managers need to collaboratively work in order to reduce effects of this stigma, and undo its damaging effects on self-esteem and QWL. In this regard, boosting self-efficacy plays a supporting role as it acts as a coping mechanism in the inter-play between Covid-19 stigma, self-esteem, and QWL.